Water Management Challenges in Coastal Polders of Bangladesh: Rethinking Institutional & Policy Issues - Huq, Hamidul; Begum, Salma; Salahuddin, Ahmad; Amin, Md. Ruhul (CGIAR System Organization, 2024)
For effective water management in coastal polders of Bangladesh, this policy brief recommends Department of Agricultural Extension (DAE) to have the overseeing role of managing Water Management Organizations (WMOs) as it has a strong local presence and a mandate for agricultural development and has been recommended by Water Management Organizations (WMOs) members to take the lead. Focus should be on empowering WMOs by outlining their rights, mandates, and responsibilities, ensuring they remain central in managing polder operations, and adjusting existing rules and regulations for membership and funding enabling WMOs to manage resources effectively, ensuring long-term sustainability without project-specific dependency. Polders and their sub-catchments should be used as primary development units, allowing agencies to work through established WMOs and avoid creating new groups for each project, thus reducing costs and enhancing impact, and designating a lead coordination agency, such as the Department of Agricultural Extension (DAE) for agriculture-based areas or the Department of Fisheries for fisheries-focused polders, would improve WMO oversight and collaboration. The Bangladesh Water Development Board (BWDB) should continue providing essential engineering support, coordinating with other agencies, and submitting rehabilitation requests based on local needs. The lead agency overseeing the WMOs in a particular polder can coordinate and request other existing actors to respond to the water management need of the WMOs. BWDB being an important actor should be available at upazila level coordination meetings concerning water management.